(untitled) (Bangladesh Journal of Pharmacology, 2014)
Metastasis is a multifactorial condition that complicates cancer treatment options and widens the target of treatment. Matrix mettalopriteinases (MMPs) of the extracellular matrix (ECM) are involved in metastasis, thus they present as potential targets in halting cancer metastasis. The study was undertaken to investigate the influence of naringenin, a naturally occurring flavonoid on the metastasis of human prostate cancer cells (PC-3 and DU145). Naringenin was observed to be effective in reducing the viability and migratory percentage of PC-3 and DU145 cells. Naringenin significantly reduced the expression and activities of the chief MMPs (MMP-2 and MMP-9) as assessed by western blotting, real-time PCR and gelatin zymography analysis. The influence of naringenin on extracellular signal-regulated kinase (ERK) -ERK1/2 was analysed by western blotting. The results indicated that naringenin was able to effectively inhibit ERK1/2. Naringenin exposure also significantly suppressed the levels of reactive oxygen species (ROS). Naringenin thus stands as an effective chemotherapeutic agent for prostate cancer treatment that could be further explored.